Las redes sociales y su incidencia en el proceso de enseñanza- aprendizaje en bachillerato general unificado - Laverde Amores, Liliana Esperanza (2017)
The research project about social networks and its incidence in the teaching-learning process was developed under the premise of diagnosing those factors that influence the use of social networks as didactic resources. The problem that was addressed in the research development is the lack of knowledge and use of social networks from the educational perspective by educational actors such as teachers and students. For this, the problem, the justification and the objectives of the research were based on the same variables that are related to social networks and the teaching - learning process. The methodological design applied during the execution of the research project was framed in the quantitative approach, combined with the bibliographical and field research that allowed to reach an exploratory level of the research. The population was 45 students, 10 teachers and the survey technique and the questionnaire instrument were applied with the objective of knowing the respective perceptions of the educational community regarding the level of knowledge, utility, didactic contribution and use of the networks in the teachers and students of the Secondary school” levels. As a contribution of research, the knowledge and use of social networks is revealed, so that readers have direct knowledge of its use as a didactic tool and can apply it in future cultural, social or any other research. The results of the research process have allowed the conclusion that teachers and students have a low level of knowledge and use of social networks for educational purposes, so this methodological strategy is not applied within the educational institution and it is necessary that in the Future actions will be developed for the improvement of the educational quality based on the use of the new information technologies that are available today.